(3QaY TCf GdMHTGfs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd HYV Ydi HYV hGdUdGI hGdSdGe Ydi SjOfG eMeO Edi Cf jMTQ GdfGS ddYQV gPG cJGH hVYJg ai aVd GdMHT eQJH Ydi ebOeI hSHY aUhd hNGJeI hSejJg QaY TCf GdMHTGf s
(3BNQgG (B:s
(3CNHQJfi Ce GdaVd HfJ eMeO Yf CHj SYjO GdNOQi bGd cGf QShd Gddg Udi Gddg Ydjg hSde EPG Sde ef UdGJg bGd SHMGf QHc QH GdYRI YeG SUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf Je QaY TCf GdMHTGf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdJGQjNs